Hubungan Karakteristik Kepribadian Dengan Perilaku Caring Perawat Dalam Pelayanan Di RSUD Kembangan Tahun 2023 - Arief Wahyudi; Indri Sarwili; Ahmad Rizal (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
A hospital is an organization that, with all its health facilities, is expected to help patients improve their health and achieve optimal healing both physically, psychologically and socially. One profession that has an important role in maintaining the quality of health services is nursing. Nursing is the activity of providing care to individuals, families, groups or communities, whether sick or healthy, because nurses in carrying out nursing practice must always improve the quality of service by following developments in science and technology through education and training according to their field. Work. This research is a type of quantitative research with a cross-sectional design approach. The results of the analysis show that the Chi Square value for extroverted personality characteristics is 0.030 and introverted personality is 0.019, indicating that there is a relationship between personality characteristics and nurses' caring behavior. Based on the characteristics of the respondents, it is known that the majority of respondents are women, with the largest age range being 22-40 years, the dominant education level is D-III nursing and the majority of respondents are single. The results of the chi-square analysis showed that the significant relationship between personality characteristics (extroversion and introversion) has major implications for nursing practice and human resource management in health care settings. A deep understanding of these interrelationships provides a foundation for improving the quality of nursing care, managing balanced care teams, and personalizing approaches to providing care to patients.